Advancing the European Green Deal with industrial policy - Roman Stöllinger (FIW - Research Centre International Economics, 2023)
The case for green industrial policy is strong and it is the obvious instrument to induce the structural transformation towards an emission-free economy. At the core of such a transformation lies the decarbonisation of the energy system. The industrial policy effort required to achieve the ambitious net zero objective in the European Green Deal (EGD) can be divided into three policy tasks: expanding renewable energy sources, raising energy efficiency across sectors and developing new technologies for industrial production processes where clean technologies are not available yet. While the first two tasks can rely on cost-competitive technologies and the required investment costs could in the long run pay for themselves, the third task constitutes formidable technological challenges that need to be tackled with a mission-oriented industrial policy. The industrial policy package employed ought to be a mix of public investments, green subsidies coupled with appropriate environmental regulations and an industrial mission for developing net zero industrial technologies. Importantly, with investment costs estimated at 1.75% of GDP per year, achieving the objectives of the EGD seems feasible also from a financial perspective. Despite this optimistic tone, the EGD is far from being a safe bet, and its success can easily be threatened by a plethora of factors, including opposition by vested interests or geopolitical confrontations.
Keywords: 330